NiFe Layered Double-Hydroxide and Cobalt-Carbon Composite as a High-Performance Eletrocatalyst for Bifunctional Oxygen Electrode. Issue 12 (1st January 2015) - Wang, Qian; Zhou, Debi; Yu, Huazhang; Zhang, Zejie; Bao, Xinjun; Zhang, Fangfang; Zhou, Mingda
Abstract : A novel non-precious composite catalyst containing NiFe layered double hydroxide (NiFe LDH) and cobalt-carbon composite (CoC) was prepared for bifunctional oxygen electrode. The structure and morphology of the composite was characterized by X-ray diffraction (XRD) and scanning electron microscopy (SEM). Electrochemical performance was tested by electrochemical impedance spectroscope (EIS) and linear sweep voltammetry (LSV) in 6 M KOH electrolyte. The oxygen electrode with NiFe LDH-CoC/AB shown excellent electrocatalytic activity for oxygen evolution reaction (OER) and oxygen reduction reaction (ORR) with the current density of 289, 41 mA cm −2 recorded at 0.70, −0.20 V vs. Hg/HgO, respectively, significantly higher than Pt/C electrode (70 mA cm −2, 30 mA cm −2 ). Tested at the current density of 40 mA cm −2 with 2 h per cycle in a zinc air battery, the bifunctional oxygen electrode exhibited unexpected cycling stability in 200 cycle periods with stable charge/discharge voltages of 2.05 V and 1.05 V.